The Usefulness of DNA Sequencing After Extraction by Whatman FTA Filter Matrix Technology and Phenotypic Tests for Differentiation of Candida albicans and Candida dubliniensis - Kiraz, Nuri; Oz, Yasemin; Aslan, Huseyin; Muslumanoglu, Hamza (SPRINGER, 2014)
Since C. dubliniensis is similar to C. albicans phenotypically, it can be misidentified as C. albicans. We aimed to investigate the prevalence of C. dubliniensis among isolates previously identified as C. albicans in our stocks and to compare the phenotypic methods and DNA sequencing of D1/D2 region on the ribosomal large subunit (rLSU) gene. A total of 850 isolates included in this study. Phenotypic identification was performed based on germ tube formation, chlamydospore production, colony colors on chromogenic agar, inability of growth at 45 A degrees C and growth on hypertonic Sabouraud dextrose agar. Eighty isolates compatible with C. dubliniensis by at least one phenotypic test were included in the sequence analysis. Nested PCR amplification of D1/D2 region of the rLSU gene was performed after the fungal DNA extraction by Whatman FTA filter paper technology. The sequencing analysis of PCR products carried out by an automated capillary gel electrophoresis device. The rate of C. dubliniensis was 2.35 % (n = 20) among isolates previously described as C. albicans. Consequently, none of the phenotypic tests provided satisfactory performance alone in our study, and molecular methods required special equipment and high cost. Thus, at least two phenotypic methods can be used for identification of C. dubliniensis, and molecular methods can be used for confirmation.
Keywords: Candida dubliniensis; Identification; Phenotypic methods; DNA sequencing; HIV-INFECTED INDIVIDUALS; POSITIVE PATIENTS; PREVALENCE; YEAST; ARGENTINA; COLONIZATION; COLLECTION; TRANSPLANT; KUWAIT; Mycology